Management of Mummification by Cervicotomy in HolsteinFriesian Crossbred Cow - J, Arunpandian; Kumar, Brijesh; Nawab, Khalander; Kohli, Kalpendra; Srivastava, Neeraj (The Indian Journal of Animal Reproduction, 2024)
A mummified foetus was delivered by cervicotomy after the failure of hormonal therapy in a six-year-old, pluriparous, Holstein Friesian crossbreed cow.